What makes court‐referred mediation effective?. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this paper is to obtain insight into court‐referred mediation in the Israeli Labor Courts, by analyzing its processes and outcomes, as a function of tactics used by both the disputants and the mediator.Design/methodology/approach – Observation of 103 court‐referred mediations, for each of which a detailed process and outcome were documented. Data on disputants' refusal to participate in the mediation was also collected. At the end of each mediation case, disputants were given a questionnaire in which they expressed their satisfaction with the outcome and their evaluation of the mediator's contribution.Findings – A low rate of refusal to participate in court‐referred mediation was found. Also, the higher the ratio of soft tactics to pressure tactics employed (by all parties involved) during the process, the higher the rate of agreements. Mediators use significantly more soft tactics than disputants, and are more active in using tactics. The two significant variables that predict the mediation's agreement are the ratio between soft tactics to pressure tactics used by all parties, and mediator contribution to the process.Practical implications – The significant role of soft tactics in the process, outcome, and satisfaction of court‐referred mediation may serve as a guideline for disputants and mediators.Originality/value – This unique research, which examines the impact of tactics on court‐referred mediation, may provide added and significant theoretical insight into its process and outcome, as well as a better understanding of other "hybrid" (compulsory at the beginning, voluntary at the end) mediations. Acknowledgements : The author is grateful to The Israeli Ministry of Industry, Trade and Labor; the Henry Crown Institute of Business Research in Israel; and the Tel Aviv University Research Authority, which supported this research. Special thanks are due to the former president of the Israeli Labor Court – Steve Adler – who enabled this unique research under the auspices of the Labor Court.